Estimation maximum sustainable of skipjack fish in the waters of Ternate Island - Taher, Al Hasim; Tangke, Umar; Namsa, Djabaluddin (Sekolah Tinggi Ilmu Pertanian Wuna, 2020)
This study aims to determine the productivity of skipjack fish in the waters of Ternate Island. Optimum efforts that produce maximum catch and still maintain stock biomass in equilibrium conditions. Fishing activities are activities carried out to get several catches, to meet demand as a source of food. The demand causes an economic cycle where profits and losses will occur so that fishing activities will be carried out by increasing fish production to achieve maximum profits by fishing businesses. Production and effort data obtained from the Ternate Archipelago Fisheries Port (PPN) and related agencies in the past 5 years (2012-2016) experienced fluctuations. Catches per unit of capture effort (CPUE), reflecting the comparison between the catch and the effort spent. The catch in principle is the output of the fishing activity, while the effort that is needed in principle is input from the fishing activity. CPUE calculations must be standardized for fishing gear first because based on production data there is more than one fishing gear commonly used to catch skipjack fish. It can be seen that in 2013 and 2014 the level of utilization of skipjack fish resources was in the optimal utilization category because the range of skipjack fish production was between 74% to 82%, whereas in 2012 and 2016 the use of skipjack fish in a year was 65% smaller so it was categorized underexploited and in 2015 the level of utilization of skipjack fish resources has experienced overfishing because it has passed the maximum limit that has been set which is 4,252,461.31 tons/year.